1998
DOI: 10.3133/pp1594
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic habitats in relation to river flow in the Apalachicola River floodplain, Florida

Abstract: Investigations, Circulars, publications of general interest (such as leaflets, pamphlets, booklets), single copies of Preliminary Determination of Epicenters, and some miscellaneous reports, including some of the foregoing series that have gone out of print at the Superintendent of Documents, are obtainable by mail from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…Open-water communities, marshes, and wetland shrub communities were replacing bottom land hardwood swamps and croplands. Additional inferences regarding likely response of riverine systems in the southeastern USA can be drawn based on evidence regarding fish utilization of naturally occurring flooded forests (Baker et al, 1991;Killgore and Baker, 1996;Light et al, 1998) or river lakes and lentic backwaters (Baker et al, 1991). The majority of fish species occurring in rivers of this region use seasonally flooded areas, particularly forests, for feeding, spawning, nursery areas (Killgore and Baker, 1996), refugia from high velocities (Matheney and Rabeni, 1995) or other purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open-water communities, marshes, and wetland shrub communities were replacing bottom land hardwood swamps and croplands. Additional inferences regarding likely response of riverine systems in the southeastern USA can be drawn based on evidence regarding fish utilization of naturally occurring flooded forests (Baker et al, 1991;Killgore and Baker, 1996;Light et al, 1998) or river lakes and lentic backwaters (Baker et al, 1991). The majority of fish species occurring in rivers of this region use seasonally flooded areas, particularly forests, for feeding, spawning, nursery areas (Killgore and Baker, 1996), refugia from high velocities (Matheney and Rabeni, 1995) or other purposes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, of the 91 species of freshwater fish recorded for the nontidal Apalachicola or lower Chipola Rivers, 73 are known to occur in river floodplains. Fifty-one of the 73 have been collected from the Apalachicola floodplain using limited sampling gears and approaches (Light et al, 1998). Streams in this region which periodically inundate their floodplains support fish assemblages distinct from those which do not because of channel incision (Shields et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although no one has documented deepening other than downstream of the dam, parts of the river have widened during the interval between 1954 and 2004, based on comparing changes in tree-line width of the main channel at similar flow levels, the study area showed width increases from about 1-40% (Price et al, 2006). The botanical changes that the floodplain experiences, namely a drier forest composition (Light et al, 1998;Darst and Light, 2008;Stallins et al, 2010;Maxwell and Knapp, 2012;Smith et al, 2013), are thus not just due to reductions in water supply but aggravated by stage decreases for a given discharge by degradation and widening.…”
Section: The Acf Waterway or Navigation Project And Known Impactsmentioning
confidence: 91%
“…Many secondary channels become active at various flow levels. More than 300 sloughs connect to the main-stem river, with over 370 km (230 mi) of length (Light et al, 1998). The largest tributary to the Apalachicola itself (i.e., below the confluence of the Chattahoochee and Flint rivers) is the Chipola River, which drains a catchment of 3290 km 2 (1270 mi 2 ) in Florida (mostly) and Alabama, and connects with the main-stem Apalachicola about 67 and 45 km (41.5 and 28 RM) upstream of Apalachicola Bay.…”
Section: Regional Setting 21 Physical Conditionsmentioning
confidence: 99%
See 1 more Smart Citation